About some specific motions of movable operating elements in the vibroimpact roll classifier - Naduty, V.P.; Yagnyukov, V.F.; Yagnyukova, I.V. (Геотехнічна механіка, 2014)
Purpose of this study was to obtain more information on motion of movable operating elements in the vibroimpact classifier, and final purpose was to improve efficiency and productivity of the mineral processing. A considerable interest presents a kinematic scheme in which a vibrating roller made in the form of a circular cylinder rolls on the inner surface of a spring-loaded square tube all points of which move circularly under the action of unbalanced vibratory drive. The studies focused on creating an analytical function, which could describe a trajectory of the roller’s mass center as close to its original as possible. Three variants of solving this problem are described. In the first variant, the analytical construction of the function is based on the integer function in a cylindrical coordinate system, in the second - on the inverse trigonometric functions such as ( ) sinarcsin ϕ and (cosarccos ϕ) in the Cartesian coordinate system, and in the third variant – on the sum of two trigonometric functions, one of which is an exponential. The obtained results can be used for qualitative and quantitative analysis of dynamics of the movable operating elements of vibroimpact roll classifier as they can reflect nay displacements, velocities and accelerations of the pendulum points. All of these three variants are also applicable for visualization and animation of the pendulum dynamics in any user-friendly graphical environment. Метою даної статті є отримання більшої інформації про рух робочих органів віброударного класифікатора, кінцевою метою створення якого є підвищення ефективності та продуктивності обробки мінеральної сировини. Суттєвий інтерес представляє кінематична схема, де валок виконаний у вигляді круглого циліндра, що здійснює вібраційне обкатування по внутрішній поверхні підпружиненої квадратної труби, всі точки якої під дією дебалансного віброприводу здійснюють кругові рухи. Дослідження зосереджені на побудові аналітичної функції, яка максимально близько описує траєкторію руху центру мас валка. Таким чином, були запропоновані три підходи вирішення даної задачі. У першому випадку аналітична побудова функції заснована на функції виділення цілої частини виразу в циліндричній системі координат, у другому - на зворотних тригонометричних функціях типу ( ) sinarcsin ϕ та ( ) cosarccos ϕ в декартовій системі координат, в третьому - на сумі двох тригонометричних функцій, одна з яких є показовою. Отримані результати можуть бути використані для якісного та кількісного аналізу динаміки робочих органів валкового віброударного класифікатора, так як можуть відображати переміщення, швидкості і прискорення точок маятника такого типу. Всі три варіанти також можуть бути застосовані для візуалізації та анімації динаміки розглянутого маятника в будь-якому зручному для користувача графічному середовищі. Цель этой статьи состоит в том, чтобы получить больше информации о движении рабочих органов виброударного классификатора, конечной целью создания которого является повышение эффективности и производительности переработки минерального сырья. Существенный интерес представляет кинематическая схема, где валок выполнен в виде круглого цилиндра, совершающего виброобкатывание по внутренней поверхности подпружиненной квадратной трубы, все точки которой под действием дебалансного вибропривода осуществляют круговые движения. Исследования сосредоточены на построении аналитической функции, максимально приближенной к описанию траектории движения центра масс валка. Таким образом, были исследованы три подхода решения данной задачи. В первом случае аналитическое построение функции основано на функции выделения целой части выражения в цилиндрической системе координат, во втором – на обратных тригонометрических функциях типа ( ) sinarcsin ϕ и (cosarccos ϕ) в декартовой системе координат, в третьем – на сумме двух тригонометрических функций, одна из которых является показательной. Полученные результаты могут быть использованы для качественного и количественного анализа динамики рассматриваемых рабочих органов валкового виброударного классификатора, так как могут отражать перемещения, скорости и ускорения точек такого типа маятника. Все три варианта также применимы для визуализации и анимации динамики рассматриваемого маятника в любой удобной для пользователя графической среде.